BLOOD SUPPLEMENTATION WITH VITAMINS INCREASES THE FERTILITY OF Anopheles darlingi (DIPTERA: CULICIDAE) - Tavares Cabral, Naiara; de Almeida e Silva, Alexandre (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Anopheles darlingi is one of the main vectors of human malaria in Brazil. Female mosquitoes use blood from vertebrates to produce their eggs and larvae. Blood composition, including vitamins, may alter fecundity and fertility, impacting mass production in the laboratory. Thus, the objective of this work was to evaluate the effect of blood supplementation with vitamins on the reproductive parameters of An. darlingi. Mosquito females were collected in a rural area of Porto Velho, and a blood meal was given in the field, adding different amounts of multivitamins in concentrations between 1 and 0.01%. The number of engorged mosquitoes and, subsequently, other variables such as survival up to oviposition, proportion of mosquitoes laying eggs, number of eggs and larvae produced were recorded. Engorgement, survival, and proportion of females laying eggs, as well as egg production, except in females supplemented with 1% of the multivitamin, were not altered by supplementation. However, the number of larvae produced increased significantly (about 20%) in females supplemented with 0.01% compared to control (no vitamins added). The present results suggest that general supplementation by vitamins increases the fertility of An. darlingi.